Training and its Impact on Employee Performance: A Study on Nepalese Local Level Government Offices’ Employees - G.C., Ramesh (Madhyabindu Journal, 2022)
Training is an integral part of the human resource management function. The efficiency or performance of an employee can be enhanced by providing time-to-time training. The effort put from the side of an organization also brings the effectiveness of the training. Similarly, the number of trainings conducted and the content, as well as the duration of the training, has also the relation in impact on the performance of employees. The paper is also concerned with the impact of training on employees’ performance among the local level government employees of Nepal. The paper has surveyed the 300 local level employees of three districts of Nepal, namely; Chitwan, Nawalpur, and Parasi. The study found that the local level governments’ employees think that their performance is mainly influenced by off-the-job training and the effort done from the side of an organization while conducting a training program.